The Use of Pentaploid Crosses for the Introgression of Amblyopyrum muticum and D-Genome Chromosome Segments Into Durum Wheat - Othmeni, Manel; Grewal, Surbhi; Hubbart-Edwards, Stella; Yang, Caiyun; Scholefield, Duncan; Ashling, Stephen; Yahyaoui, Amor; Gustafson, Perry; Singh, Pawan K.; King, Ian P.; King, Julie (Frontiers in Plant Science, 2019)
The wild relatives of wheat provide an important source of genetic variation for wheat improvement. Much of the work in the past aimed at transferring genetic variation from wild relatives into wheat has relied on the exploitation of the ph1b mutant, located on the long arm of chromosome 5B. This mutation allows homoeologous recombination to occur between chromosomes from related but different genomes, e.g. between the chromosomes of wheat and related chromosomes from a wild relative resulting in the generation of interspecific recombinant chromosomes. However, the ph1b mutant also enables recombination to occur between the homoeologous genomes of wheat, e.g. A/B, A/D, B/D, resulting in the generation of wheat intergenomic recombinant chromosomes. In this work we report on the presence of wheat intergenomic recombinants in the genomic background of hexaploid wheat/Amblyopyrum muticum introgression lines. The transfer of genomic rearrangements involving the D-genome through pentaploid crosses provides a strategy by which the D-genome of wheat can be introgressed into durum wheat. Hence, a pentaploid crossing strategy was used to transfer D D-genome segments, translocated with either the A- and/or the B-genome, into the tetraploid background of two durum wheat genotypes Karim and Om Rabi 5 in either the presence or absence of different Am. muticum (2n = 2x = 14, TT) segments. Translocations were monitored in backcross generations to the durum wheat parents via multicolour genomic in situ hybridisation (mc-GISH). Tetraploid lines carrying homozygous D-genome introgressions, as well as simultaneous homozygous D- and T-genome introgressions, were developed. Introgression lines were characterised via KASP markers and multicolour fluorescence in situ hybridisation (FISH). Results showed that new wheat sub-genomic translocations were generated at each generation in progeny that carried any Am. muticum chromosome segment irrespective of the linkage group that the segment was derived from. The highest frequencies of homoeologous recombination were observed between the A- and the D- genomes. Results indicated that the genotype Karim had a higher tolerance to genomic rearrangements and T-genome introgressions compared to Om Rabi 5. This indicates the importance of the selection of the parental genotype when attempting to transfer/develop introgressions into durum wheat from pentaploid crosses.